2022
DOI: 10.1371/journal.pone.0265620
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the experience of veterans who require lower limb amputation in the veterans health administration

Abstract: Purpose There is limited qualitative research on the experience of patients undergoing lower limb amputation due to chronic limb threatening ischemia (CLTI) and their participation in amputation-level decisions. This study was performed to understand patient lived experiences related to amputation and patient involvement in shared decision making. Materials and methods Phenomenological interviews were conducted with Veterans 6–12 months post transtibial or transmetatarsal amputation due to CLTI. Interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…While our findings are consistent with pooled analyses of low-to-average atherogenic risk populations, 36 it is possible that our disparate findings in the CKD cohort may relate to the higher amputation risk observed in Veterans. 37 We also found that GLP1a vs. DPP4i use was associated with higher risk of amputation in those without CKD. Given that few studies have directly compared GLP1a vs. DPP4i use on amputation risk, further confirmatory studies are needed.…”
Section: Discussionmentioning
confidence: 55%
“…While our findings are consistent with pooled analyses of low-to-average atherogenic risk populations, 36 it is possible that our disparate findings in the CKD cohort may relate to the higher amputation risk observed in Veterans. 37 We also found that GLP1a vs. DPP4i use was associated with higher risk of amputation in those without CKD. Given that few studies have directly compared GLP1a vs. DPP4i use on amputation risk, further confirmatory studies are needed.…”
Section: Discussionmentioning
confidence: 55%
“…The shrapnel or mine explosions often lead to amputation, impacting various body parts such as the head, neck, chest, abdomen, eyes, and upper limbs of veterans [1]. Complications arising from limb amputation manifest in both pre and post-prosthesis insertion stages.…”
Section: Introductionmentioning
confidence: 99%